Characterization of outcomes 1 year after endoscopic thermal vapor ablation for patients with heterogeneous emphysema - Herth, Felix (The International journal of chronic obstructive pulmonary disease, 2012)
Introduction: Endoscopic lung volume reduction has been developed as a therapeutic option for advanced emphysema. Six-month results following treatment with endoscopic thermal vapor ablation (InterVapor™; Uptake Medical, Tustin, CA) were described previously, and here we report observations from the 12-month assessment. Methods: Two multicenter, international, single-arm trials of InterVapor (unilateral upper lobe treatment) in patients with upper lobe predominant emphysema were conducted. Inclusion criteria: forced expiratory volume in 1 second (FEV1) 15%-45% predicted, residual volume > 150%, total lung capacity > 100%, 6-minute walk distance (6MWD) >140 m, and diffusing capacity for carbon monoxide > 20% predicted. Efficacy endpoints: spirometry, body plethysmography, lung volumes by high-resolution computed tomography, St George’s Respiratory Questionnaire, modified Medical Research Council dyspnea scale, and 6MWD. All adverse events were collected and independently adjudicated. Results: Forty four patients were treated at a mean (standard deviation) age of 63 (5.6) years, FEV1 0.86 mL (0.25 mL) (n = 22 men and 22 women). Mean (standard deviation) changes from baseline at 12 months were: FEV1 86.2 mL (173.8 mL), St George’s Respiratory Questionnaire −11.0 (14.0) units, treated lobar volume from high-resolution computed tomography −751.8 mL (653.9 mL), residual volume −302.8 mL (775.6 mL), 6MWD 18.5 m (63.7 m), and modified Medical Research Council dyspnea scale score −0.83 (0.97) (P < 0.05 for all except 6MWD). Improvements were numerically larger at 6 versus 12 months. GOLD stage III and IV patients had similar outcomes at 6 months; however, improvements relative to baseline were numerically higher in GOLD stage IV patients. Larger improvements were observed in patients with higher heterogeneity. In total, 39 serious adverse events were reported in 23 patients with 10 events in 8 patients between 6 and 12 months. Conclusion: Unilateral lobar InterVapor treatment of heterogeneous emphysema improved lung function and health outcomes 1 year following treatment. The magnitude of improvement was larger at 6 months compared to 12 months. Improvements relative to baseline continue to be exhibited at 12 months despite the expected disease related decline over time. Clinical trials: NCT 01041586 and NCT 01102712
Gesehen am 11.06.2018